Monitoring Population Parameters for Fisheries Management: I. Species Composition, Abundance and Distribution Patterns of Fishes in Paya Bungor - Ambak, Mohd Azmi; Mohammad Mohsin, Abu Khair (1986)
A one year direct monitoring study offish populations was conducted in Paya Bungor. The lake comprised 12 families and 43 species of freshwater fishes. The cyprinids dominated the fish community, contributing to about 54% followed by the catfishes (16%). More species were recorded in the northern part of the lake. Riverzne species accounted for more than 80% of the species composition in Paya Bungor. A high percentage of predatory species (49%) was also observed. Amblyrhynchichthys truncatus was the most abundant species (33%) followed by Thynnichthys thynnoides (20%) and Puntius schwanenfeldii (18%). Together with 12 other cyprinids, they made up more than 90% of the total catch. Catfishes, comprising 7 species constituted only 1.4%. The general pattern of seasonal abundance indicate that more fishes are found in the months of January, March, June and September while less fish occur in the months of February, May, August and September. This pattern zs relat.ed tv fluctuations in water levels, WL, water temperature, T, and conductivity, C, as exemplified by the equation: Population abundance, p = -886 + 135 WL + 23.77 T - 0.151 C. The heterogenous fish population in Paya Bungor exhibit spatial and temporal patterns of distribution. The species in Paya Bungor are log-normally distributed with the distribution curve as follows: . 2 S(R) = 5.366 exp -(0.365)